A Trait-Based Protocol for the Biological Control of Invasive Exotic Plant Species - Zhang, Hui; Jiang, Kai; Zhao, Yang; Xing, Yuting; Ge, Haijie; Cui, Jie; Liu, Tiedong; Wang, Chen (Frontiers in Ecology and Evolution, 2021)
Selecting appropriate native species for the biological control of invasive exotic plants is a recurring challenge for conservationists, ecologists, and land managers. Recently developed trait-based approaches may be an effective means of overcoming this challenge. However, we lack a protocol and software platform that can be used to quickly and effectively select potential native plant species for performing biological control of the invasive exotic plant species. Here, our study introduces a protocol and a software program that can be used for trait-based selection of appropriate native plant species for performing biocontrol of invasive exotic plant species. In particular, we illustrate the effectiveness of this software program and protocol by identifying native species that can be used for the biological control of Leucaena leucocephala (Lam.) de Wit, a highly invasive plant species found in many parts of the world. Bougainvillea spectabilis was the only native species selected by our software program as a potential biocontrol agent for L. leucocephala. When separately planting 4 seedlings of B. spectabilis and two unselected species (Bombax ceiba, and Ficus microcarpa) as neighbors of each individual of L. leucocephala for 3 years, we found that B. spectabilis, which was functionally similar to the invasive L. leucocephala, significantly limited the invasion of the latter, while the unselected native plant species could not. That was because all the seedling of B. spectabilis survived, while half seedlings of unselected species (B. ceiba and F. microcarpa) died, during the experimental period when planted with L. leucocephala seedlings. Moreover, the growth of L. leucocephala was restricted when planted with B. spectabilis, in contrast B. ceiba and F. microcarpa did not influence the growth of L. leucocephala. Overall, our software program and protocol can quickly and efficiently select native plant species for use in the biological control of invasive exotic plant species. We expect that this work will provide a general protocol to perform biological control of many different types of invasive exotic plant species.